Ore genesis of the Xiadian gold deposit, Jiaodong Peninsula, East China: Information from fluid inclusions and mineralization. (8th November 2017) - Liu, Jianchao; Wang, Jinya; Liu, Yang; Tian, Jingxiang; Li, Xiuzhang; Zhang, Haidong
Abstract : Orebodies in the Xiadian gold deposit in the Jiaodong Peninsula, China are mainly hosted in the Mesozoic granitoids, controlled structurally by the Zhaoyuan–Pingdu Fault Zone, and occur as disseminated and cataclastic altered type. Four mineralization stages were identified as follows: quartz–pyrite stage (I), gold‐bearing fine‐grained pyrite–quartz stage (II), polymetallic sulfide–quartz stage (III), and quartz–carbonate stage (IV). Quartz was classified as including quartz granules with dentation boundaries (I), cataclastic quartz grain assemblages (II and III), and rod‐like quartz grains (IV). Petrography, laser Raman analysis, and microthermometry of fluid inclusions in these stages (in both tunnel and borehole samples) reveal (a) CO2 –H2 O fluid inclusions (C–H type), (b) CO2 –H2 O ± CH4 fluid inclusions (C–H–CH4 type), and (c) aqueous fluid inclusions (H type). Fluid immiscibility caused by fluid mixing caused rapid precipitation of gold. The ore‐forming fluid of the Xiadian gold deposit evolves from an H2 O–CO2 –NaCl ± CH4 system with medium temperature and salinity to an H2 O–NaCl system with low temperature and salinity, from CO2 ‐rich to CO2 ‐poor in composition and from a mixture of magmatic water with increasing meteoric water as δ 18 OH2O values. Sulphur isotope compositions suggest a mixed source of ore metal, and the Jiaodong Group may be a major source for sulphur. Fluid parameters of borehole samples indicate that there is the same fluid system for Au precipitation at different depths and fault gouge with poor permeability may play a crucial role in forming a relatively closed semi‐open space for Au precipitation. Integrating the data obtained from the studies including regional geology, ore geology, and fluid inclusions and stable isotope geochemistry, the Xiadian gold deposit is concluded as an orogenic‐type gold deposit formed in the tectonic transition from compression to extension.